Uniwersytet podczas informacyjnego tsunami - Wróbel, Szymon (Człowiek i Społeczeństwo, 2020)
Luciano Floridi and Nick Srnicek claims that with a decline in manufacturing profitability, capitalism has turned to data as one way to maintain economic growth in the face of a slow production sector. In the twenty-first century data have become central to firms and their relations with workers and customers (Floridi, 2013; Srnicek 2017). The platform has emerged as a new model, capable of extracting and controlling immense amounts of data, and with this shift we have seen the rise of monopolistic firms. We are told that today we are living in an age of massive transformation. Platforms, big data, additive manufacturing, advanced robotics, machine learning, and the internet of things – create our current living environment. In the presented text I am going to ask what is the place of the university in such a new digital constellation? What are universities for in the time of platform capitalism? My main line of reasoning follows to idea of “entrepreneurial state”. An innovative university is understood as an analogue of an “entrepreneurial state”. Mariana Mazzucato has convincingly demonstrated that developments like railways, the internet, computing, supersonic flight, space travel, satellites, pharmaceuticals, voice-recognition software, nanotechnology, touchscreensand clean energy have all been nurtured and guided by states, not corporations. During the golden postwar era of research and development, two-thirds of research and development was publicly funded. High-risk inventions and new technologies are too risky for private capitalists to invest in (Mazzucato, 2014; Srnicek, Williams, 2015). Socializing of the risk and privatization of profits – this is the main climate of “non-innovative capitalism”.